Pengaruh Social Media Marketing dan Accesbility Terhadap Minat Kunjung Kembali Wisatawan di Pantai Lon Malang - Sari, Febby Fatika; Aguilika, Deykha (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
The purpose of this study is to examine how social media marketing and accessibility affect revisit interest. The method used in this research is quantitative method. Statistical Product and Service Solutions (SPSS) version 25 was used to process and analyze data collected from 105 respondents through questionnaires. Simultaneously, social media marketing and accesbility variables have a positive and significant influence on return visit interest, and partially both variables have a significant effect on return visit interest. Therefore, a highly visible social media marketing campaign and easy access will influence visitors' propensity to return.